Implementation of Supervision of Notaries Who Violate the Notaries Code of Ethics in the Form of Promoting Positions Through Electronic Media in Tegal Regency - Wulan Dhari Asriningrum, Tri; Ma'ruf, Umar (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
As public officials, notaries hold a distinguished position (officium nobile) and are therefore obligated to uphold the integrity and dignity of their profession. However, developments in information technology and social media have given rise to self-promotion practices that violate the Notary Code of Ethics. This study aims to analyze the implementation of supervision of notaries who violate the code of ethics by promoting their positions through electronic media in Tegal Regency. The research method used is a sociological juridical approach with data collection techniques through interviews with the Regional Notary Supervisory Board of Tegal Regency and literature studies. The research results indicate that supervision is carried out through a mechanism of examining public reports, clarifying the situation with the notary concerned, and imposing sanctions ranging from written warnings to temporary dismissal from professional organizations. Obstacles faced include a lack of awareness among notaries regarding the ethical boundaries of electronic media use and weak preventive oversight. Supervision of notaries who violate the code of ethics through electronic media in Tegal Regency has been ongoing, but is not yet optimal. Increased dissemination of the code of ethics, strengthening the role of the Notary Honorary Council, and stricter regulations regarding notaries' use of social media are needed.